A study of designers' cognitive activity in design informational phase - Mougenot,C; Bouchard,C; Aoussat,A (2007)
In the purpose of developping better design-support tools and improving design education, design cognition studies describe designers' mental strategies for solving design problems. So far, the first steps toward a description of designers' strategies have shown that analogies are widely used in the ideas generation phases of design process. But the very early stages of design, in the transition from brief reception to idea generation, still remain uncompletely understood and described; our study aims at exploring the way designers handle visual information beforing reaching the Eureka moment. Experiments were carried out with four professional designers from car-design European companies. The participants were invited to browse two media, printed magazines and Internet, in order to retrieve 'inspirational' images and to associate lexical descriptions to the selected images. Then in a later task, the participants had to illustrate an assigned design brief with pictures they found through online picture-search engines. The main findings deal with designers' creativity and designers' kansei: (1) In the early phases of design, the activity of browsing information sources is a combination of a generic process, shared by all designers, and individual strategies involving the designer's subjectivity. (2) New media, such as the Internet, surely impact the information phase of the early stages of design projects. Designers modify their creative strategies to adapt to the media capabilities.